Association of Ovarian Structures, Uterine Characteristics and Cervico-vaginal Mucus Attributes with Conception in Dairy Cows - Khanoria, Neha; Singh, Madhumeet; Sharma, Akshay (The Indian Journal of Animal Reproduction, 2022)
This study was conducted to evaluate the association between ovarian structures, uterine characteristics and physical attributes of cervico-vaginal mucus (CVM) with conception rate in normal cyclic dairy cows (N=20) at estrus. Different physical parameters of CVM at estrus such as quantity, consistency, color, pH, Spinnbarkeit value and fern pattern were evaluated. Transrectal ultrasonography was done at estrus to carry out the morphometry of follicles and uterine horns as well as following artificial insemination, the mid-cyclic corpus luteum size and functionality were assessed on the 10th day using B-mode and color Doppler ultrasonography. Among the physical parameters, significantly higher (p
Keywords: Cervicovaginal mucus; dairy cows; preovulatory follicle; spinnbarkeit; estrus